FUNCTIONAL ROLE OF VIMENTIN'S CYSTEINE IN XIST-MEDIATED EMT INHIBITION IN BREAST CANCER - Jayanti; Melisa; Arnando; Mur'ah; Noviyanti (Journal of Stem Cell Research and Tissue Engineering, 2025)
Breast cancer is the most commonly diagnosed malignancy among women worldwide and a leading cause of cancer-related mortality, primarily due to its high metastatic potential. One mechanism underlying metastasis is the epithelial-to-mesenchymal transition (EMT), which enhances cancer cell mobility, invasiveness, and resistance to treatment. Vimentin, a type III intermediate filament protein, is a hallmark of EMT and plays a structural and regulatory role in cytoskeletal organization and cellular stress responses. Recent studies have highlighted the importance of a single cysteine residue at position 328 (C328) in vimentin, which functions as a redox-sensitive site influencing filament dynamics. However, the role of C328 in cancer progression remained largely unexplored. This literature review investigates the effect of a single amino acid substitution—C328 to serine (C328S)—on breast cancer cell behavior, focusing on findings published between 2020 and 2025, sourced from PubMed and Google Scholar. Evidence from MCF-7 breast cancer cell models reveals that expression of C328S-VIM induces morphological changes, cytoskeletal disorganization, and increased proliferation, migration, and invasion. Notably, C328S-VIM upregulates the long non-coding RNA XIST, which promotes EMT, estrogen independence, and stem-like properties. These findings indicate that the native C328 residue serves a tumor-suppressive function, partly through modulation of XIST activity. Overall, this review presents a novel insight into how a single amino acid mutation in vimentin can reprogram breast cancer cells toward a more aggressive and stem-like phenotype. The study highlights C328 as a potential therapeutic target and broadens our understanding of the molecular mechanisms driving breast cancer progression.